Supply of immigrant entrepreneurs and native entrepreneurship - Keshar M. Ghimire (IZA Journal of Development and Migration, 2021)
Using nationally representative data from the United States, the author estimates the causal impact of immigrant entrepreneurship on entrepreneurial propensities of natives. The author draws data from the Annual Social and Economic Supplement of the Current Population Survey and uses within-state variation in supply of immigrant entrepreneurs for identification. To address concerns of endogeneity in the supply of immigrant entrepreneurs, the author takes advantage of a quasi-experiment provided by the State Children's Health Insurance Program. While the Ordinary Least Squares estimates indicate a positive effect, the Two Stage Least Squares estimates suggest that, on average, there is no significant effect of immigrant entrepreneurs on native entrepreneurship. Moreover, there is no net effect on subgroups of natives separated by skill level. There is also some evidence that immigrant entrepreneurs may "crowd-in" Blacks into certain types of self-employment. These results are in contrast to the significant negative impact suggested by the previous literature.
Keywords: J61; F22; L26; 330; entrepreneurship; immigration; self-employment; incorporated and unincorporated businesses; State Children's Health Insurance Program